Characterization of hybrid pultruded structural products based on preforms. (1st May 2018) - Silva, F.J.G.; Baptista, A.; Pinto, G.; Campilho, R.D.S.G.; Ribeiro, M.C.S.
Abstract: Pultrusion is a widely known technique for production of constant cross-section profiles, such as bars, L-shape or T-shape profiles, as well as structural tubes in polymer matrix composite materials. In some applications, requirements are demanding for profiles able to provide better thermal or sound insulation or needing a slightly higher moment of inertia without increasing the ratio between weight and strength. In such cases, hybrid pultruded profiles with core based on preforms are a possible solution. After obtaining prototypes according to the methodologies described in a previous work, and as a complement to that work, it is necessary to verify if the properties of these hybrid profiles correspond to the initial expectations, by performing destructive and non-destructive tests. Thus, tensile, compression and bending tests were performed, in order to verify the mechanical benefits achieved through the core introduction into the hollow profile and to analyse the added value brought by these new products. These values, once properly validated, can be added to existing databases related to structural calculation programs, enabling to get the adequate values for calculations regarding this kind of profiles. In addition, thermal and acoustic insulation tests were performed, in order to quantify the physical improvements achieved regarding these properties, which are extremely important in specific applications linked to the civil construction and public works, among many others. The cored profiles showed a strong adhesion between the profile and any kind of core tested as well as improved properties in terms of thermal insulation and moment of inertia. However, the sound insulation did not present significant improvements, probably due to GFRP profile external rigidity and consequent reflection. Highlights: A novel kind of hybrid GFRP pultruded profiles was produced based on cork or polyurethane preforms. Adhesion between the GFRP pultruded profile and core was tested, showing very good results. Bending tests allow realize that hybrid profiles have increased flexural resistance relatively to usual profiles. Thermal insulation was improved by the inclusion of cork or polyurethane cores. Acoustic insulation was also improved in the case of GFRP pultruded profiles with cork or polyurethane cores.